DYNAMICS OF SOME HEALTH INDICES DURING THE SCHOOL YEAR AMONG CHILDREN, LEARNING ACCORDING TO THE PROGRAM OF THE INTERMEDIATE COMPREHENSIVE AND WALDORF SCHOOL - Yu.A. Gavrilova; E.M. Spivak ("Paediatrician" Publishers LLC, 2007)
.